Driving sustainable energy transition: Understanding residential rooftop solar photovoltaic adoption in Malaysia through a behavioural analysis - Sook-Theng Lam; Kian-Meng Yap; Keat-Hoe Yeoh (Renewable and Sustainable Energy Transition)
Malaysia aims to achieve carbon neutrality by 2050, addressing climate change by transitioning to low-carbon electricity. With the power sector contributing 36 % of carbon emissions in 2019, solar photovoltaic (PV) is a key solution, given Malaysia's abundant sunshine. While government roadmaps emphasize solar PV, the retrofit market remains underexplored. This study investigates barriers to rooftop solar PV adoption in existing houses using the unified theory of acceptance and use of technology (UTAUT2), examining economic, environmental, social, technological, and regulatory factors. Combining quantitative surveys and in-depth interviews, it identifies drivers and obstacles, providing actionable insights for policymakers and stakeholders to accelerate adoption and support Malaysia's decarbonization goals. Findings from SEM indicate that Performance Expectancy (PE, β = 0.311, p < 0.001), Price Value (PV, β = 0.245, p = 0.006), Facilitating Conditions (FC, β = 0.311, p < 0.001) and Environmental Concern (EC, β = 0.253, p < 0.001) significantly predict Behavioral Intention (BI) to adopt rooftop solar PV systems. Social Influence (SI, β = −0.111, p = 0.165), Effort Expectancy (EE, β = −0.098, p = 0.266) and Hedonic Motivation (HM, β = 0.082, p = 0.167) were statistically insignificant. The model explained 88.6 % of the variance (R² = 0.886), with high sampling adequacy (KMO = 0.949). However, qualitative findings reveal that Social Influence plays a significant role in shaping BI, highlighting the importance of peer recommendations and community perceptions. These integrated findings highlight the importance of considering economic, social, and environmental factors in the adoption process. This study expands the applicability of UTAUT2 to new technology research, particularly for rooftop solar PV, providing valuable insights for policymakers and stakeholders to promote solar PV adoption and support Malaysia's decarbonization goals.